Full stack testing : a practical guide for delivering high quality software - Mohan, Gayathri (Sebastopol, CA : O'Reilly Media, 2022)
Testing is a critical discipline for any organization looking to deliver high-quality software. This practical book provides software developers and QA engineers with a comprehensive one-stop guide to testing skills in 10 different categories. You'll learn appropriate strategies, concepts, and practical implementation knowledge you can apply from both a development and a testing perspective for web and mobile applications. Author Gayathri Mohan offers examples of more than 40 tools you can use immediately. Software testing professionals and beginners alike will acquire the skills to conduct tests for performance, security, and accessibility, including exploratory testing, test automation, cross-functional testing, data testing, mobile testing, and more. You'll also learn to combine them in continuous integration pipelines to gain faster feedback. With this guide, you'll be able to tackle challenging development workflows with a focus on quality.
Introduction to full stack testing -- Manual exploratory testing -- Automated functional testing -- Continuous testing -- Data testing -- Visual testing -- Security testing -- Performance testing -- Accessibility testing -- Cross-functional requirements testing -- Mobile testing -- Moving beyond in testing -- Introduction to testing in emerging technologies.
Includes index.
Keywords: Computer software -- Testing; Computer software -- Testing; Software; Testen